Mental Health: Criteria for Evaluation of the Digital Applications as Facilitative Tools of Public Psychoeducation - Oleh Starovoitenko; Mykola Sliusarevskyi; Lidiya Chorna (Insight: the psychological dimensions of society, 2025)
In recent decades, digital applications that support mental health have gained global usage due to their undeniable advantages in the widespread dissemination of psychoeducational content and the facilitation of psychoeducation processes. Numerous studies on the effectiveness of such psychoeducational tools provide fragmented information regarding their advantages and disadvantages. This complicates the selection of specific applications as optimal for use in each particular psychoeducational request, both for the mental health professionals and for the end users of the psychoeducational content. The aim of the research was to define a set of criteria and indicators for evaluating and comparing different types of digital psychoeducational tools. This is valuable for facilitating their informed selection and application in psychological assistance and self-help practices. Aligning the content component of psychoeducation, such as psychoeducational information that is particularly sensitive and relevant to the population, especially in wartime conditions, with the formal component of the psychoeducation process, namely, digital, stigma- free means of content dissemination, significantly increases the potential for facilitating and enhancing the effectiveness of psychoeducational activities among the population. Methods. Based on a synthesis of scientific research on the subject, using inductive qualitative analysis, expert evaluations, and statistical methods to assess their consistency, a set of criteria was identified for evaluating the facilitative potential of digital psychoeducational applications. Results.The criteria for evaluating digital psychoeducational applications include user accessibility, adaptiveness and focus level of the tool, user interest protection, interactivity of user engagement, and support for psychoeducational content assimilation. The rank correlation indicators of expert evaluations for the selected criteria demonstrate overall consistency, thereby confirming their applicability for the informed selection of a particular tool based on specific user needs. The highest level of agreement among expert evaluations was observed for the criteria of interactivity of user engagement and user interest protection. Discussion and Conclusions. The authors of the article demonstrated the possibility of developing a set of criteria for evaluating digital psychoeducational applications to be used as a universal tool for comparing such applications. This, in turn, will enhance the effectiveness of psychoeducational initiatives based on digital applications already at the planning stage of such initiatives.